The Relationship Between Dietary Patterns and Total Blood Cholesterol Levels at Lecturers Muhammadiyah University of Parepare - Nur Rahmadhani B. Bambona; Haniarti Haniarti; Nurlinda Nurlinda (Indonesian Health Journal, 2022)
Today's lifestyle has changed very significantly. This is due to the low balance between activity and exercise in the diet, so health problems often arise. One of the lifestyle changes that have occurred is a change in diet which should be maintained by consuming healthy foods. However, nowadays, many prefer to consume ready-to-eat food (fast food), which contains much-saturated fat, especially for office workers. This study aims to determine the relationship between diet and total blood cholesterol levels in Muhammadiyah Parepare University lecturers. This study used an analytic observational research method with an accidental sampling technique using the solving formula. A sample of 67 people was obtained. This study's results indicated a relationship between diet and total blood cholesterol levels in Muhammadiyah Parepare University lecturers using the Chi-Square test and obtained p = 0.001 < ? = 0.005. Based on the research that has been done, the results show a relationship between diet and total cholesterol levels in Muhammadiyah Parepare University lecturers using the Chi-Square test and the value of p = 0.001 < ? = 0.005. It is recommended to regulate diet and the amount of food that contains fat and carry out periodic checks such as nutritional status, hypertension, blood sugar levels, uric acid and cholesterol regularly at least once every six months to reduce consumption of cholesterol-producing fats